Implementation of Behavior Based Robotics on Hexapod Legged Robot Based on Room Mapping - Salsabila, Zahra; Widodo, Nuryono Satya (Peneliti Teknologi Teknik Indonesia, 2023)
The Indonesian Fire Fighting Robot Contest (KRPAI) has a mission to extinguish fires quickly, with various kinds of points and bonuses to be taken. The robot used in this research is a 6-legged robot (Hexapod). The problem faced today is the robot's ability to navigate the room, the robot still has to enter the same room, especially in room 1 (a room with 2 doors) so that the Arbitrary Start bonus or Variable Door location which prohibits the robot from entering the same room cannot be obtained. There is also a Room Factor bonus obtained using the JTS (Segment Distance) method which is an additional bonus when the robot walks outside the room. It is necessary to develop a room mapping algorithm with behavior based so that the robot can get maximum points. The main sensor used is the IMU BNO055 sensor as a robot direction orientation sensor, as well as a proximity sensor as a wall search sensor, so that the robot can know the direction when leaving and exploring the room, knowing the starting room, and ensuring the next room entered is a different room. The results of the test successfully made the robot take maximum points in the race.